(untitled) (Impetus, 2020)
This article aims to analyze the variables that influence the offensive phases of men’s professional football teams in the first division of Bogotá, during the 2017 Finalization Tournament, when four teams from the Colombian capital were playing in the first division tournament (Millonarios, Santa Faith, Equity and Tigers). Seven variables are used for each of the offensive actions analyzed: partial result, beginning of the offensive pattern, players who participate, number of individual offensive techniques, game zones, attack phases and completion of the offensive game, through an observational analysis that allows distinguish if there are offensive tactical patterns in the teams analyzed and if some of the variables directly affect the ways of attacking. Using the LINCE registration software, five matches of each team were analyzed, observed sequentially (matchday 1, 5, 10, 15 and 20) for a total of 20 matches. The results affirm that in Colombian soccer the offensive tactical patterns are very short and have no analogy between them. In addition, direct attacks and stopped ball plays are manifested as the most common strategy used by teams to attack.